Perencanaan Sumur Resapan Untuk Mereduksi Limpasan Permukaan Pada Perumahan Mangga Raya Residence Tenayan Raya Pekanbaru - Arneni, Arneni; Suprayogi, Imam; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The increasing number of people in the new Pekanbaru city caused land ordinance changes,resulting ina reduction of water in the region so that when rainfall increased and drainage capacity were not optimum, surface could be impended. A region that had similar problems in 2017 Mangga Raya Residence is severe surface runoff asa result of rainfall according to the fact that in September to Desember ,reducing existing housing to a level was reduced because the nonoptimum cotton wedges in the study were done in order to minimize the surface runoff in the region,building receipts for each housimg to reduce runoff and in an effort to raise water from the calculation and imaging of the planning of the resply wells from 1 m(8m) in diameter,it is a maximum diameter of the requirements for the planning of the picket wells issued by SNI-2017 and permeable value permeable bags 0,0000556 m/dtk. The permeable wells is divided into 2 wells for 1 house with 4 meters each in depth ,according to what is named in a SNI-8456-2017,a well and a water repellate trench after your plan the charge that comes out to 0,88 m³/dt is draining his discharge out of neither more than drainage capacity 0,9 m³/dt.fees needed to be spent for the gouging wlls with a depth of 8 m are devided into 2 in 1 house is Rp.9.570.193. Keywords: Reduction Runoff, Reenactment Wells,Mangga Raya Residence